THE ROLE OF RECEPTORS TO ESTROGEN AND PROGESTERONE IN PRESCRIPTION OF HORMONAL THERAPY TO PATIENTS WITH BREAST CANCER IN DIFFERENT AGE GROUPS - Protcenko, O.S.; Polyakova, O.V.; Ponomarchuk, R.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The role of receptors to estrogen and progesterone in prescription of hormonal therapy to patients with breast cancer in different age groups is investigated on materials of Institute of medical radiology by named by S. P. Grigoriev AMSU. It is established, that presence of receptors to an estrogen and progesterone differs depending on age of patients. In premenopausal age estrogenic receptors with weak positive reaction prevail, in postmenopausal age quantity of progesterone receptors increases, whereas at senile age in 80 % of cases receptors are absent. Received data is necessary for taking into account in prescription of hormonal therapy to patients with breast cancer.